Mechanisms of radiation in a bat group from the genus Pipistrellus inferred by phylogeography, demography and population genetics - Hulva, P; Fornůsková, A; Chudárková, A; Evin, A; Allegrini, B; Benda, P; Bryja, J (Molecular ecology, 2010)
Here, we present a study of the Pipistrellus pipistrellus species complex, a highly diversified bat group with a radiation centre in the Mediterranean biodiversity hotspot. The study sample comprised 583 animals from 118 localities representatively covering the bats' range in the western Palearctic. We used fast-evolving markers (the mitochondrial D-loop sequence and 11 nuclear microsatellites) to describe the phylogeography, demography and population structure of this model taxon and address details of its diversification. The overall pattern within this group includes a mosaic of phylogenetically basal, often morphologically distant, relatively small and mostly allopatric demes in the Mediterranean Basin, as well as two sympatric sibling species in the large continental part of the range. The southern populations exhibit constant size, whereas northern populations show a demographic trend of growth associated with range expansion during the Pleistocene climate oscillations. There is evidence of isolation by distance and female philopatry in P. pipistrellus sensu stricto. Although the northern populations are reproductively isolated, we detected introgression events among several Mediterranean lineages. This pattern implies incomplete establishment of reproductive isolating mechanisms in these populations as well as the existence of a past reinforcement stage in the continental siblings. The occurrence of reticulations in the radiation centre among morphologically and ecologically derived relict demes suggests that adaptive unequal gene exchange within hybridizing populations could play a role in speciation and adaptive radiation within this group.
Keywords: fylogeografie; Animals; Středomoří; Genetics, Population; Mediterranean Region; zvířata; Phylogeography; mikrosatelitní repetice; DNA, Mitochondrial; populační genetika; mitochondriální DNA; Chiroptera; Microsatellite Repeats